Reevaluation of Design Flood Discharge under Climate Change: Future Peak Flow Projection in the Johor River Watershed, Malaysia - Yazawa, Taishi (Journal of Interdisciplinary Perspectives, 2025)
This study aims to develop the intensity-duration-frequency (IDF) relationships for the historical (1979-2003) and future (2075-2099) scenarios, and to evaluate changes in estimated design flood values and return periods in the Johor River Basin, Malaysia. The hydrological frequency analysis, using historical and future rainfall scenarios, was then conducted to estimate changes in design flood values (peak flows). The Hydrological Simulation Program-FORTRAN was used for runoff simulations. The changes in the return periods of the estimated flood values were assessed using the cumulative distribution function mapping method. As an example of the results under the future scenario, a design flood value with a 5-day rainfall duration will become 992.1 m3/s (i.e., an increase of 58.1% compared to the historical scenario) based on the future IDF relationship. The return period for this value is 282.8 years based on the historical IDF relationship. This means that the current planning scale, e.g., the 100-year return period commonly used in Malaysia, might not be adequate and should be extended to prevent and/or mitigate the damage from devastating floods under climate change.